Conteúdos conceituais nas coleções de história para o ensino médio : o que muda e o que permanece com a intervenção do programa nacional do livro didático (1997- 2005)? - Souza, Kleber Luiz Gavião Machado de (2011)
The aim of this research is to know the changed and permanent aspects of writing of History related to the evaluated and approved textbooks distributed by ―Programa Nacional do Livro Didático para o Ensino Médio (PNLEM)‖ through analysis of its conceptual metahistoric and substantive concepts. The methodology used was the analysis of the rules set up by announcements of programme on historical concepts considered important. So, we carry out the analysis of present and past collections to the programme in order to know if PNLEM was responsible for an improvement in their conceptual contents as ever identified by researchers on teaching History when they worked on the ―Programa Nacional do Livro Didático para o Ensino Fundamental‖. Our meaningful time goes from 1997 to 2005. The methodological procedures of Analysis of Content by Laurence Bardin (1977) were used to cathegorize the contents extracted in historical propositions in the textbook. The importance of this is to know how much the public policies influence in History textbooks in this teaching level.